The Buddha’s Journey from Peshawar to Zurich: Handling the Complex Challenges of Coordination - Akhlaq, Syed Junaid (Journal of Pakistan Administration, 2021)
International collaboration in the fields of contemporary cultures and cultural heritage helps propagate and preserve national history, memory and identity. While taking many forms and shapes, such collaborations provide both challenge as well as opportunities to appraise capacities of cultural organizations. Thus, such international collaboration demands unconventional leadership that is able to unravel complexities of processes for establishing coordination among various stakeholders. The protagonist of this case study, Mahmood, served as the focal person in this international project between Pakistan and Switzerland in his capacity as the Director General of the Department of Archeology and Museums (DOAM). He was responsible for dealing with policy, rules and regulations relating to the loaning of cultural artifacts. The whole episode entailed and exhibited leadership that was able to maintain a steady flow of coordination and communication between important stakeholders i.e. DOAM, Directorate of Archaeology and Museums (DAM), Khyber Pakhtunkhwa, Swiss Development & Cooperation Agency (SDC), Islamabad, and Rietberg Museum Zurich (RMZ), Switzerland.
Keywords: Buddha’s Journey; Peshawar; Zurich; international collaboration